Functional Outcomes of Stroke Patients Admitted to a Tertiary Hospital in the Western Cape, South Africa - I. Parekh; A. Rhoda (AOSIS, 2013)
Individuals with stroke often experience functional limitationssuch as the inability to walk independently. There are several factors that areassociated with functional outcome post stroke. The aim of the study was thereforeto determine functional outcomes and factors influencing functional outcomes ofstroke patients admitted to a South African tertiary hospital. A longitudinal designwas used to obtain the data. A convenient sampling method was used to recruit100 participants. Data was collected on admission, discharge and two months poststroke, using the National Institute of Health Stroke Scale, Barthel Index and asocio-demographic and medical profile data sheet. The data was analyzed usingSPSS version 18 and SAS version 9. Tobit analysis was used to determine the factors influencing functional outcomes at dischargeand two months post stroke. The necessary ethical clearance was obtained prior to commencement of the study. Stair climbing,mobility and transfers were the functional activities that the majority of the participants could not perform independently. Age andseverity of stroke significantly influenced the functional outcomes at discharge and two months post stroke. Factors such as ageand stroke severity should therefore be considered when planning rehabilitation interventions for stroke patients in this setting.